2023
DOI: 10.1186/s12940-022-00954-9
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution associated acute respiratory inflammation and modification by GSTM1 and GSTT1 gene polymorphisms: a panel study of healthy undergraduates

Abstract: Epidemiological evidence has linked air pollution with adverse respiratory outcomes, but the mechanisms underlying susceptibility to air pollution remain unclear. This study aimed to investigate the role of glutathione S-transferase (GST) polymorphism in the association between air pollution and lung function levels. A total of 75 healthy young volunteers aged 18–20 years old were recruited for six follow-up visits and examinations. Spirometry was conducted to obtain lung function parameters such as forced vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Research suggests that OS could be the main potential cause of respiratory system injuries due to air pollution. Numerous studies have investigated the relationships among atmospheric particulates (such as PM 2.5 and PM 10 ), gaseous pollutants (such as O 3 , SO 2 , NO 2 , and CO), and various OS biomarkers [18]. Li et al [19] found that the exposure time of PM 2.5 and SO 2 was positively correlated with the level of OS biomarkers.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that OS could be the main potential cause of respiratory system injuries due to air pollution. Numerous studies have investigated the relationships among atmospheric particulates (such as PM 2.5 and PM 10 ), gaseous pollutants (such as O 3 , SO 2 , NO 2 , and CO), and various OS biomarkers [18]. Li et al [19] found that the exposure time of PM 2.5 and SO 2 was positively correlated with the level of OS biomarkers.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Li et al [19] found that the exposure time of PM 2.5 and SO 2 was positively correlated with the level of OS biomarkers. Zeng et al [18] demonstrated that exposure to PM 10 is associated with elevated levels of inflammation biomarkers, such as interleukin (IL)-6, IL-8, tumor necrosis factor (TNF)-α, and 8-epi-pgf2α, which is closely related to OS.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Additionally, no research has yet looked at the combined impact of PM2.5 and genetic polymorphisms on the risk of CVD. Prior research indicates that genetic polymorphism should be taken into account when exploring the effects of pollutants on various physiological and immunological processes in humans, especially in cardiovascular diseases and respiratory diseases [11,12]. For instance, a panel study revealed that individuals with the glutathione Stransferase mu 1 genotype are more vulnerable to air pollution [12].…”
Section: Introductionmentioning
confidence: 99%